2018
DOI: 10.1111/rego.12212
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the institutionalization of private sustainability governance in a changing coffee sector

Abstract: The potential of transnational private governance initiatives to constitute effective alternatives to state‐led regulation of global value chains rests on their ability to scale up and become institutionalized in a given sector. This study examines whether such institutionalization has occurred in the coffee sector, the commodity with the most widespread adoption of certified products and over 30 years’ experience of private governance, and tests hypotheses on facilitating and inhibiting conditions. It finds t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
74
0
4

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 77 publications
(79 citation statements)
references
References 87 publications
(201 reference statements)
1
74
0
4
Order By: Relevance
“…The variety of relationships between producers, traders and roasters within the coffee GVC/GPN may suggest the existence of 'limited governance' (Fitter & Kaplinsky, 2001) or 'multipolar governance' (Ponte & Sturgeon, 2014). However, Grabs (2018) has recently shown that roasters and retailers like Nestle and Starbucks have begun rolling out their own certification schemes, leading to sustainability initiative adapting their strategies towards roasters and retailers from one of confrontation to competition. Though there remain numerous stakeholders occupying governance roles within the coffee GVC/GPN, there is a global tendency towards buyer-driven governance.…”
Section: Governance Dynamics In the Coffee Gvc/gpnmentioning
confidence: 99%
“…The variety of relationships between producers, traders and roasters within the coffee GVC/GPN may suggest the existence of 'limited governance' (Fitter & Kaplinsky, 2001) or 'multipolar governance' (Ponte & Sturgeon, 2014). However, Grabs (2018) has recently shown that roasters and retailers like Nestle and Starbucks have begun rolling out their own certification schemes, leading to sustainability initiative adapting their strategies towards roasters and retailers from one of confrontation to competition. Though there remain numerous stakeholders occupying governance roles within the coffee GVC/GPN, there is a global tendency towards buyer-driven governance.…”
Section: Governance Dynamics In the Coffee Gvc/gpnmentioning
confidence: 99%
“…In 2018, the institutional settings of the global value chain for coffee are characterized by limited state intervention, but with an expanding system of private regulation by both corporate firms and NGOs. This is most notable through the expansion of various sustainability programs orchestrated along the value chain between consumers and producers (Jaffee, ; Panhuysen & Pierrot, ; Levy et al ., ; Grabs, ). Low world coffee prices (especially during the period 2000 to 2004) led to widespread reports of extreme poverty in coffee‐growing communities and what was identified as a ‘global coffee crisis’ (Osorio, ; Vega et al ., ; Bacon, ; Daviron & Ponte, ).…”
Section: The Global Value Chain For Coffeementioning
confidence: 99%
“…Various applications of a GVC or global commodity chain (GCC) approach to the coffee industry over the last few decades (inter alia Talbot, ; Talbot, ; Ponte, ; Talbot, ; Daviron & Ponte, ; Neilson, ; Neilson & Pritchard, ; Grabs, ) have consistently identified a range of characteristic chain dynamics. The fundamental geography of coffee production and trade has, until very recently, remained largely consistent with earlier colonial patterns.…”
Section: The Global Value Chain For Coffeementioning
confidence: 99%
See 2 more Smart Citations